Early Childhood Teacher Research: From Questions to Results - Castle, Kathryn (Routledge, Taylor & Francis Group, 2011)
What is early childhood teacher research and why is it important? How does a teacher researcher formulate a research question and a plan for doing research? How do teachers apply research results to effect change? "Early Childhood Teacher Research" is an exciting new resource that will address the sorts of questions and concerns that pre- and in-service teachers of young children frequently have when engaging in teacher research. Accessible and interactive, this book touches upon the important issues every early childhood teacher should know--the uniqueness of early childhood teacher research, reasons for doing it, and how to do it. In this comprehensive guide, Kathryn Castle explores each stage of teacher research, from conceptualization, generating research questions, identifying data sources, gathering and analyzing data, interpreting results, sharing results, to taking action based on results. Special features included in each chapter: (1) Teacher Researcher Journal prompts for the reader to record ideas for research questions and to develop a plan for doing research; (2) From the Field provides rich examples of real life early childhood teacher researchers and their perspectives on doing teacher research; (3) Reflections ask readers to pause and think deeply about relating content to their own situations; and (4) Exploration of additional content, websites, resources, and activities are located in each chapter to help the reader go further in constructing their knowledge of teacher research. The following chapters are contained in this book: (1) What Is Early Childhood Teacher Research? (2) What is the Purpose of Early Childhood Teacher Research?; (3) Where Will Puzzlement and Wondering Lead? (4) Why Plan? (5) Data, Data, Who Has the Data? (6) What Do Data Reveal? (7) Who Might Be Interested? (8) What Comes After Research Is Completed? Appended are: (1) Ethnographic Description of a First Grade Classroom; (2) Reflection on National Board Video of Class Discussion; (3) Teacher Interview Transcript; and (4) The Wonder of Learning Newsletter Article. A glossary is included.